PETG composite material, surface hardening liquid and injection molding method thereof

By spraying the hardening liquid during the injection molding process of PETG composite material and controlling its thickness and spraying time, the problem of easy scratches in the injection molding and use of PETG composite material is solved, and its tensile strength, impact strength and scratch resistance are improved. sex.

CN119388672APending Publication Date: 2025-02-07CHONGQING SHICHUANGXIN POLYMER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411455075.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

PETG materials are prone to scratches during injection molding and use, affecting the aesthetics of the product, and their mechanical properties are different from other types of highly transparent plastics, limiting their application.

Method used

PETG composite materials and their injection molding methods are used to spray hardening liquid in the injection molding cavity of the injection mold, and control the thickness and spray time of the hardening liquid during the injection molding process, the hardness of the product surface is improved and the risk of scratching is reduced.

Benefits of technology

It improves the tensile strength, impact strength, service life and scratch resistance of PETG composite materials, and enhances the mechanical properties and aesthetics of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090230990000021
    Figure BDA0005090230990000021
  • Figure BDA0005090230990000031
    Figure BDA0005090230990000031
  • Figure BDA0005090230990000041
    Figure BDA0005090230990000041
Patent Text Reader

Abstract

The invention discloses an injection molding method of a PETG composite material. The injection molding method comprises the following steps: spraying a release agent on the injection molding surface of an injection mold; closing the injection mold; spraying hardening liquid into an injection molding cavity of the injection mold in a vaporific manner, wherein the thickness of the hardening liquid in the injection molding cavity of the injection mold is not more than 0.02 mm; injecting a molten PETG composite material liquid into an injection molding cavity of the injection mold; cooling the injection mold, opening the mold, and taking out an injection product. The PETG composite material comprises the following components in parts by mass: 100 parts of PETG, 1-3 parts of an ester exchange inhibitor, 0.3-1 part of hydrotalcite, 0.1-0.2 part of a light stabilizer, 0.7-0.9 part of a maleic anhydride grafted compatilizer, 0.2-0.6 part of an antioxidant, 3-5 parts of a crystallization accelerant and 0.5-3 parts of an anti-hydrolysis agent. The hardening liquid comprises the following components in parts by mass: 2-5 parts of modified inorganic nanoparticles, 18-20 parts of oligomeric resin, 5-7 parts of a dispersing agent, 8-12 parts of thermosetting resin, 1-2 parts of an antioxidant, 5-8 parts of PETG and 18-22 parts of solvent resin. The tensile strength, the impact strength, the service life and the scratch resistance of the prepared product are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of injection molding materials and injection molding processing technology, and in particular to a PETG composite material, a surface hardening liquid and an injection molding method thereof. Background Art

[0002] PETG (polyethylene terephthalate-1,4-cyclohexanedimethanol) is a transparent, non-crystalline copolyester. The commonly used comonomer of PETG is 1,4-cyclohexanedimethanol (CHDM), and its full name is polyethylene terephthalate-1,4-cyclohexanedimethanol. PETG is a product of terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) through ester exchange. Compared with PET, it has more 1,4-cyclohexanedimethanol comonomer, and compared with PCT, it has more ethylene glycol comonomer. Therefore, the performance of PETG is very different from that of PET and PCT.

[0003] PETG sheet has outstanding toughness and high impact strength. Its impact strength is 3 to 10 times that of modified polyacrylates. It has a wide processing range, high mechanical strength and excellent flexibility. Compared with PVC, it has high transparency, good gloss, easy printing and environmental protection advantages. However, the mechanical properties of PETG are somewhat different from other plastics with high transparency, such as PMMA (polymethyl methacrylate), PS (polystyrene), PC (polycarbonate), etc., which limits its application. At the same time, due to its poor toughness, it is easy to produce scratches during injection molding demoulding and use, affecting the appearance of the product. Summary of the invention

[0004] In view of the above-mentioned defects of the prior art, the object of the present invention is to provide a PETG composite material, a surface hardening liquid and an injection molding method thereof, which can improve the tensile strength, impact strength, service life and scratch resistance thereof.

[0005] The objective of the present invention is achieved through such technical solution:

[0006] A PETG composite material injection molding method comprises the following steps:

[0007] Spraying a release agent on the injection surface of the injection mold;

[0008] Clamping the injection mold;

[0009] A hardening liquid is sprayed in a mist form into the injection cavity of the injection mold, and the thickness of the hardening liquid in the injection cavity of the injection mold does not exceed 0.02 mm;

[0010] Injecting molten PETG composite material liquid into the injection cavity of the injection mold;

[0011] After the injection mold cools down, open the mold and take out the injection molded product.

[0012] Furthermore, in the step of "mist spraying hardening liquid into the injection cavity of the injection mold", the hardening liquid is sprayed out using a high-pressure nozzle, and the nozzle is located at the largest cavity in the injection cavity of the mold; after the step of "mist spraying hardening liquid into the injection cavity of the injection mold", the injection cavity of the injection mold is vacuumed.

[0013] Furthermore, before evacuating the injection cavity of the injection mold after the step of “mist spraying the hardening liquid into the injection cavity of the injection mold”, high-pressure clean gas is injected into the injection cavity of the injection mold for 1 to 2 seconds within 0.1 to 0.5 seconds after the mist spraying of the hardening liquid is completed, and the pressure of the gas does not exceed 5 times the atmospheric pressure; the volume of the high-pressure clean gas injected into the injection cavity of the injection mold per second is 2 to 4 times the volume of the injection cavity of the injection mold.

[0014] Furthermore, before the step of "injecting the molten PETG composite material liquid into the injection cavity of the injection mold", the hardening liquid remains on the inner surface of the injection cavity of the injection mold for no less than 2 seconds.

[0015] PETG composite material, including the following components calculated by mass:

[0016]

[0017] The PETG is prepared by polycondensation using CHDM as a raw material.

[0018] Furthermore, the ester exchange inhibitor is a sulfate inhibitor; the light stabilizer is ZX-70; the antioxidant is 1076; the crystallization promoter is RS-735, and the anti-hydrolysis agent is BK-503.

[0019] The hardening liquid comprises the following components calculated in parts by mass:

[0020]

[0021]

[0022] Furthermore, the oligomeric resin includes polyurethane acrylate and thermoplastic acrylic resin, and the oligomeric polyurethane acrylate and the thermoplastic acrylic resin each account for 50%.

[0023] Furthermore, the antioxidant is butylated toluene; the solvent resin is phenolic resin; the dispersant is fatty amine polyoxyethylene ether; and the thermosetting resin is thermosetting polyimide.

[0024] Furthermore, the modified inorganic nanoparticles are a mixture of nano-silicon dioxide and nano-calcium carbonate; the proportion of the nano-calcium carbonate is 50%.

[0025] Due to the adoption of the above technical solution, the present invention has the following advantages:

[0026] 1. Taking PETG as the main material, adding specific other materials to obtain a comprehensive plastic material with a transparency not much different from that of pure PETG material. Compared with pure PETG material, it improves tensile strength, impact strength and service life.

[0027] 2. During the injection molding process of the PETG composite material, spray the hardening liquid in the injection molding cavity. After the injection molding is completed, the hardening liquid and the PETG composite material are integrated to improve the hardness of the product surface and reduce the probability and degree of scratches on the product surface during demolding and use.

[0028] 3. Spray the hardening liquid in the injection molding cavity in a mist-like manner, which not only improves the injection molding efficiency, but also effectively controls the thickness of the hardening liquid to ensure the overall quality of the injection molding product.

[0029] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the embodiments.

[0031] The specifications and models of the raw materials used in the following examples are as follows:

[0032] PETG: Made by polycondensation using CHDM as raw material;

[0033] Transesterification inhibitors: calcium sulfate;

[0034] Hydrotalcite: Japan Sekisui HT-V;

[0035] Light stabilizer: ZX-70;

[0036] Antioxidants: 1076;

[0037] Crystallization accelerator: RS-735;

[0038] Anti-hydrolysis agent: BK-503.

[0039] Embodiment 1:

[0040] A PETG composite material injection molding method comprises the following steps:

[0041] Spraying a release agent on the injection surface of the injection mold;

[0042] Clamping the injection mold;

[0043] A high-pressure nozzle is used to spray the hardening liquid into the injection cavity of the injection mold in a mist form, and the spray outlet is located at the largest cavity in the injection cavity of the mold. The thickness of the hardening liquid in the injection cavity of the injection mold does not exceed 0.02 mm;

[0044] Within 0.1 to 0.5 seconds after the hardening liquid is sprayed in a mist form, high-pressure clean gas is injected into the injection cavity of the injection mold for 1 to 2 seconds, and the pressure of the gas does not exceed 5 times the atmospheric pressure; the volume of the high-pressure clean gas injected into the injection cavity of the injection mold per second is 2 to 4 times the volume of the injection cavity of the injection mold;

[0045] Evacuate the injection cavity of the injection mold;

[0046] After the hardening liquid remains on the inner surface of the injection cavity of the injection mold for not less than 2 seconds, the PETG composite material liquid in a molten state is injected into the injection cavity of the injection mold;

[0047] After the injection mold cools down, open the mold and take out the injection molded product.

[0048] Specifically, the above-mentioned PETG composite material includes the following components calculated by mass:

[0049]

[0050] Specifically, the hardening liquid includes the following components calculated by mass:

[0051]

[0052] Embodiment 2:

[0053] A PETG composite material injection molding method comprises the following steps:

[0054] Spraying a release agent on the injection surface of the injection mold;

[0055] Clamping the injection mold;

[0056] A high-pressure nozzle is used to spray the hardening liquid into the injection cavity of the injection mold in a mist form, and the spray outlet is located at the largest cavity in the injection cavity of the mold. The thickness of the hardening liquid in the injection cavity of the injection mold does not exceed 0.02 mm;

[0057] Within 0.1 to 0.5 seconds after the hardening liquid is sprayed in a mist form, high-pressure clean gas is injected into the injection cavity of the injection mold for 1 to 2 seconds, and the pressure of the gas does not exceed 5 times the atmospheric pressure; the volume of the high-pressure clean gas injected into the injection cavity of the injection mold per second is 2 to 4 times the volume of the injection cavity of the injection mold;

[0058] Evacuate the injection cavity of the injection mold;

[0059] After the hardening liquid remains on the inner surface of the injection cavity of the injection mold for not less than 2 seconds, the PETG composite material liquid in a molten state is injected into the injection cavity of the injection mold;

[0060] After the injection mold cools down, open the mold and take out the injection molded product.

[0061] Specifically, the above-mentioned PETG composite material includes the following components calculated by mass:

[0062]

[0063]

[0064] Specifically, the hardening liquid includes the following components calculated by mass:

[0065]

[0066] Embodiment 3:

[0067] A PETG composite material injection molding method comprises the following steps:

[0068] Spraying a release agent on the injection surface of the injection mold;

[0069] Clamping the injection mold;

[0070] A high-pressure nozzle is used to spray the hardening liquid into the injection cavity of the injection mold in a mist form, and the spray outlet is located at the largest cavity in the injection cavity of the mold. The thickness of the hardening liquid in the injection cavity of the injection mold does not exceed 0.02 mm;

[0071] Within 0.1 to 0.5 seconds after the hardening liquid is sprayed in a mist form, high-pressure clean gas is injected into the injection cavity of the injection mold for 1 to 2 seconds, and the pressure of the gas does not exceed 5 times the atmospheric pressure; the volume of the high-pressure clean gas injected into the injection cavity of the injection mold per second is 2 to 4 times the volume of the injection cavity of the injection mold;

[0072] Evacuate the injection cavity of the injection mold;

[0073] After the hardening liquid remains on the inner surface of the injection cavity of the injection mold for not less than 2 seconds, the PETG composite material liquid in a molten state is injected into the injection cavity of the injection mold;

[0074] After the injection mold cools down, open the mold and take out the injection molded product.

[0075] Specifically, the above-mentioned PETG composite material includes the following components calculated by mass:

[0076]

[0077] Specifically, the hardening liquid includes the following components calculated by mass:

[0078]

[0079] Embodiment 4:

[0080] A PETG composite material injection molding method comprises the following steps:

[0081] Spraying a release agent on the injection surface of the injection mold;

[0082] Clamping the injection mold;

[0083] A high-pressure nozzle is used to spray the hardening liquid into the injection cavity of the injection mold in a mist form, and the spray outlet is located at the largest cavity in the injection cavity of the mold. The thickness of the hardening liquid in the injection cavity of the injection mold does not exceed 0.02 mm;

[0084] Within 0.1 to 0.5 seconds after the hardening liquid is sprayed in a mist form, high-pressure clean gas is injected into the injection cavity of the injection mold for 1 to 2 seconds, and the pressure of the gas does not exceed 5 times the atmospheric pressure; the volume of the high-pressure clean gas injected into the injection cavity of the injection mold per second is 2 to 4 times the volume of the injection cavity of the injection mold;

[0085] Evacuate the injection cavity of the injection mold;

[0086] After the hardening liquid remains on the inner surface of the injection cavity of the injection mold for not less than 2 seconds, the PETG composite material liquid in a molten state is injected into the injection cavity of the injection mold;

[0087] After the injection mold cools down, open the mold and take out the injection molded product.

[0088] Specifically, the above-mentioned PETG composite material includes the following components calculated by mass:

[0089]

[0090] Specifically, the hardening liquid includes the following components calculated by mass:

[0091]

[0092] The products obtained in the above embodiments were tested for tensile strength, impact strength, light transmittance, weather resistance, and surface hardness. The specific test standards are as follows:

[0093] Tensile strength test: According to GB1040-2018 Determination of tensile properties of plastics, the sample size is 150mm×10mm×4mm dumbbell standard specimen;

[0094] Simple supported beam impact strength test: According to GB / T 1043.2-2018 Determination of impact properties of plastic simple supported beams Part 2: Instrumented impact test, the sample size is 80mm×10mm×4mm with a notch, room temperature;

[0095] Test of light transmittance and haze: Tested in accordance with GB / T 2410-2008 Determination of light transmittance and haze of transparent plastics.

[0096] Weather resistance test: According to GB / T 2423-2013 Procedure A method to test the weather resistance of materials (40 cycles) and ISO105-A02 to evaluate the grayscale level of discoloration,

[0097] Surface hardness test: According to GB / T 3398.2-2008 Plastic hardness determination Part 2: Rockwell hardness, the sample size is 100mm×100mm×4mm plate.

[0098] The PETG obtained by polycondensation using CHDM as raw material was injection molded into finished products in a conventional manner to form a comparative example, and was tested according to the above test.

[0099] The test results of the above embodiments and comparative examples are shown in the following table:

[0100] Example 1 Example 2 Example 3 Example 4 Comparative Example Tensile strength(Mpa) 68.15 69.82 71.14 68.57 65.4 <![CDATA[Impact strength (kJ / m 2 )]]> 7.01 6.97 6.89 7.02 6.59 Light transmittance (%) 90.51 89.21 88.58 89.65 91.71 Weather resistance (gray scale) 5 5 4 5 3 Rockwell hardness 119 121 125 122 107

[0101] It can be clearly seen from the above table that although the light transmittance of the injection molded product obtained by adopting the present invention has a certain degree of decline, the tensile strength, impact strength, service life and scratch resistance are significantly improved, and PETG products can be applied to more fields.

[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A PETG composite material injection molding method, characterized in that, The following steps are involved: Spraying a release agent on the injection surface of the injection mold; Clamping the injection mold; A hardening liquid is sprayed in a mist form into the injection cavity of the injection mold, and the thickness of the hardening liquid in the injection cavity of the injection mold does not exceed 0.02 mm; Injecting molten PETG composite material liquid into the injection cavity of the injection mold; After the injection mold cools down, open the mold and take out the injection molded product.

2. The PETG composite material injection molding method according to claim 1, characterized in that, In the step of "mist spraying the hardening liquid into the injection cavity of the injection mold", the hardening liquid is sprayed out by a high-pressure nozzle, and the spray outlet is located at the largest cavity in the injection cavity of the mold; after the step of "mist spraying the hardening liquid into the injection cavity of the injection mold", the injection cavity of the injection mold is vacuumed.

3. The PETG composite material injection molding method according to claim 2, characterized in that, After the step of "mist spraying the hardening liquid into the injection cavity of the injection mold" and before evacuating the injection cavity of the injection mold, within 0.1 to 0.5 seconds after the mist spraying of the hardening liquid, high-pressure clean gas is injected into the injection cavity of the injection mold for 1 to 2 seconds, and the pressure of the gas does not exceed 5 times the atmospheric pressure; the volume of the high-pressure clean gas injected into the injection cavity of the injection mold per second is 2 to 4 times the volume of the injection cavity of the injection mold.

4. The PETG composite material injection molding method according to claim 1, characterized in that, Before the step of "injecting the molten PETG composite material liquid into the injection cavity of the injection mold", the hardening liquid remains on the inner surface of the injection cavity of the injection mold for not less than 2 seconds.

5. The PETG composite material according to any one of claims 1 to 4, characterized in that: Includes the following components calculated by mass: The PETG is prepared by polycondensation using CHDM as a raw material.

6. The PETG composite material according to claim 5, characterized in that The ester exchange inhibitor is a sulfate inhibitor; the light stabilizer is ZX-70; the antioxidant is 1076; the crystallization promoter is RS-735, and the anti-hydrolysis agent is BK-503.

7. The hardening solution according to any one of claims 1 to 4, characterized in that: Includes the following components calculated by mass:

8. The hardening liquid according to claim 7, characterized in that: The oligomeric resin includes polyurethane acrylate and thermoplastic acrylic resin, and the oligomeric polyurethane acrylate and the thermoplastic acrylic resin each account for 50%.

9. The hardening liquid according to claim 7, characterized in that: The antioxidant is butylated toluene; the solvent resin is phenolic resin; the dispersant is fatty amine polyoxyethylene ether; and the thermosetting resin is thermosetting polyimide.

10. The hardening solution according to claim 1, characterized in that The modified inorganic nanoparticles are a mixture of nano-silicon dioxide and nano-calcium carbonate; the proportion of the nano-calcium carbonate is 50%.